(untitled) (مجلة إحالات, 2026)
This is a critical reading of one of the poetic poems that dealt with the theme of the Corona epidemic, specifically the poem “Corona between the two shores of death and survival” by the Saudi poet Abdul Rahman Al-Otel. It is a reading that invests the stylistic approach in revealing the sources of creativity and the specificity of artistic expression in this poem, and to highlight the extent of the impact of this pandemic on the language of the poem and its various levels.